The proliferation rates of HT-1080 human fibrosarcoma cells can be accelerated or inhibited by weak static and extremely low frequency magnetic fields - Bajtoš, Marek; Dang, Nhat; Lopez de Mingo, Isabel; Keller, Jason; Gurhan, Hakki; Janoušek, Ladislav; Barnes, Frank (Frontiers in Public Health, 2025)
IntroductionWeak static and low-frequency magnetic fields (MFs) have been hypothesized to influence biological systems through mechanisms involving nuclear spin coupling. This study investigates how such fields modulate the proliferation of HT-1080 fibrosarcoma cells.MethodsHT-1080 cells were exposed in vitro for 4 days to weak MFs with a 10 μT amplitude and frequencies between 12 Hz and 33 Hz, superimposed on a 45 μT static background field. Changes in cell growth, mitochondrial superoxide (O2−), calcium ion (Ca2+) concentrations, and membrane potential were measured.ResultsResults revealed that MFs could either increase or decrease fibrosarcoma cell growth in a frequency- and amplitude-dependent manner. Inversions in growth rates were observed near 16.5 Hz, where a 0.5 Hz shift or amplitude changes as small as 250 nT reversed effects relative to controls. Reversing the static field direction also inverted growth outcomes. Changes in membrane potential, Ca2+, and mitochondrial superoxide levels supported a role for bioenergetic modulation.DiscussionThese findings suggest that weak MFs affect cell proliferation through spin-dependent chemical reaction rate changes. The pronounced sensitivity of fibrosarcoma cells compared to normal fibroblasts points to potential therapeutic applications via selective MF-based modulation.